Knowledge transfer for the development of sustainable tourism: focus on offi cial Portuguese tourism websites - Borges, Maria do Rosário (2013)
To achieve development of sustainable tourism, policy makers and managers need up-to-date, accurate and relevant knowledge. Therefore, a tourism knowledge platform is essential for all stakeholders. Additionally, the internet is part of the day-to-day life of people and organisations, with all its inherent advantages. In this context, the present article features how the internet has been used by Portuguese public organisations operating in the tourism destination of the Alentejo to disseminate information about sustainable tourism. The content analysis research technique was used to evaluate information content within offi cial tourism websites with a view to sharing data and information about the overall scope of sustainable development issues. The outcomes demonstrate that these websites are not used as platforms for knowledge transfer concerning sustainable tourism.